I have basic calculus functions problem. I understand the basic concept of functions, but for some reason this problem is not working out to the correct answer.
f(g(x))
f(x)=x³+5
g(x)=x²-2
My understanding of it is as follows:
f(g(x))= (x²-2)³+5
I believe I am correct up to this point. When ever I expand the cubed expression within the parenthesis, I come up short to the correct answer.
Thank you in advance
f(g(x))
f(x)=x³+5
g(x)=x²-2
My understanding of it is as follows:
f(g(x))= (x²-2)³+5
I believe I am correct up to this point. When ever I expand the cubed expression within the parenthesis, I come up short to the correct answer.
Thank you in advance